A cross‐sectional study of factors associated with influenza vaccination in Korean cancer survivors. (25th March 2021) - Lee, Ji Eun; Shin, Dong Wook; Shin, Jinyoung; Cho, In Young; Lee, Jungkwon; Hwang, JiHye; Cho, BeLong; Song, Yun‐Mi
Abstract: Objective: To investigate factors associated with influenza vaccination in cancer survivors. Methods: Study subjects were 1, 945 Korean adult cancer survivors. Through medical record review and self‐administered questionnaires, social and medical information was collected. Influenza vaccination was defined as ever having received a flu vaccine between one year before cancer diagnosis and the survey date. Multiple logistic regression analysis was used to evaluate factors associated with influenza vaccination. Results: Overall, 60.8% of study subjects had received an influenza vaccination. Younger survivors had a significantly lower vaccination rate than did the elderly survivors (80.22% vs. 54.73%). In younger survivors, longer time elapsed since cancer diagnosis, lifestyle modification counselling during cancer treatment, adequate physical exercise (≥150 min/week) and complementary medication use were positively associated with vaccination, whereas extra‐pulmonary cancers, multimodality (≥3) cancer treatment and higher educational achievement were inversely associated. In elderly survivors, fewer factors had a positive (adequate physical exercise) or inverse (multimodality cancer treatment and current smoking) association with influenza vaccination. Conclusion: Influenza vaccination rate was suboptimal, especially among younger cancer survivors. Targeted strategies are necessary to improve influenza vaccination in cancer survivors with consideration of individual characteristics such as age, lifestyle, cancer treatment modality, cancer type and education level.